Pengaruh aplikasi pupuk hayati mikoriza dan pupuk fosfor terhadap produksi tanaman kedelai (Glycine max L. Meriil) - Panataria, Lince R; Sitorus, Efbertias; Saragih, Meylin; Sitorus, Jose (Jurnal Agrotek Ummat, 2022)
This study aims to determine the production of soybeans with the application of mycorrhizal biological fertilizers and P fertilizers on the production of soybeans (Glycine max L. Meriil). This experiment was carried out at the Experimental Garden of the Faculty of Agriculture, Indonesian Methodist University, from August–October 2018. This study used a Randomized Block Design (RAK) consisting of Mycorrhiza (M) namely M0: 0 g/plant (control); M1: 5 g/plant; M2: 10 g/plant; M3: 15g/plant and Fertilizer (P), namely P0: 0 g/plant (control); P1:0.25 g/plant; P2: 0.5 g/plant; P3: 0.75 g/plant. All treatment combinations were 12 combinations and each treatment combination was repeated 3 times. Variables observed in this study include: flowering age (days); seed production per sample (g); seed production per plot (g); dry weight of 100 seeds (g). The experimental results showed that the interaction between mycorrhizal application and application of NPK fertilizer had a significant effect on seed production per sample, seed production per plot, dry weight of 100 seeds and not significantly different with flowering age. The highest seed production per sample was found in the M3P3 treatment of 26.32 g, the highest seed production per plot was found in the M3P2 treatment of 161.80 g and the highest dry weight of 100 seeds was found in the M3P3 treatment of 25.60 g. The mycorrhizal biofertilizer application treatment showed that the fastest flowering time was found in the M3 treatment, namely 36.58 days and 36.92 days in the P (P3) fertilizer treatment.